Tetracycline, an Appropriate Reagent for Measuring Bone-Formation Activity in the Murine Model of the Streptococcus mutans-Induced Bone Loss - Hirohashi, Yuna; Kamijo, Shingo; Khan, Masud; Ikeda, Masaomi; Oki, Meiko; Matin, Khairul; Rashed, Fatma; Aoki, Kazuhiro (Frontiers in Cellular and Infection Microbiology, 2021)
Tetracycline is used as a fluorescent reagent to measure bone formation activity in bone histomorphometric analyses. However, there is a possibility to lead a different conclusion when it is used in a bacteria-infected murine model since the tetracycline is considered to work as an antibiotic reagent. There are non-antibiotic fluorescent reagents such as alizarin and calcein for measuring bone formation activity. The purpose of this study was to clarify whether tetracycline could be an appropriate reagent to measure bone formation activity in a murine bacterial model in the same way as a non-antibiotic fluorescent reagent. We used Streptococcus mutans (S. mutans), a normal inhabitant in the oral cavity and tetracycline-sensitive bacteria, for inducing the bacterial model. The murine bacterial model was generated by intravenously inoculating S. mutans to the tail vein, followed immediately by the injection of the first fluorescent reagent, and the second one was injected 2 days prior to euthanization. After one day of inoculation with S. mutans, the subcutaneously injected alizarin had a similar colony count derived from the liver and the bone marrow tissue compared to the phosphate buffered saline (PBS)-injected control group. On the other hand, subcutaneous injection of tetracycline led to a significantly lower colony count from the liver compared to alizarin- or calcein-injected group. However, on day seven, after S. mutans intravenous injections, bone mineral density of distal femurs was significantly reduced by the bacteria inoculation regardless of which fluorescent reagents were injected subcutaneously. Finally, S. mutans inoculation reduced bone-formation-activity indices in both the tetracycline-alizarin double-injected mice and the calcein-alizarin double-injected mice. These results suggested that a one-time injection of tetracycline did not affect bone formation indices in the S. mutans-induced bone loss model. Tetracycline could be used for measuring bone formation activity in the same way as non-antibiotic fluorescent reagent such as calcein and alizarin, even in a tetracycline-sensitive bacterium-infected model.